2021
DOI: 10.1021/acs.chemmater.1c03255
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Functionalization of Nickel Phosphide Nanocrystals with Aryl-Diazonium Salts

Abstract: Covalent functionalization of Ni2P nanocrystals was demonstrated using aryl-diazonium salts. Spontaneous adsorption of aryl functional groups was observed, with surface coverages ranging from 20-96% depending on the native reactivity of the salt as determined by the aryl substitution pattern. Increased coverage was possible for low reactivity species using a sacrificial reductant. Functionalization was confirmed using thermogravimetric analysis, FTIR and X-ray photoelectron spectroscopy. The structure and ener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 131 publications
3
19
0
Order By: Relevance
“…We attributed the difference to the changes in the surface dipole, which is determined by the dipole moment at the surface–ligand interface and the ligand molecular structures 10 . Therefore, the use of metal salt treatment provided a step to adjust the work function of colloidal NCs 31 . The removal of insulating organic layers and shortening interparticle distances help to enhance the electronic exchange coupling energy in NC solids and increase their packing density 12 .…”
Section: Resultsmentioning
confidence: 99%
“…We attributed the difference to the changes in the surface dipole, which is determined by the dipole moment at the surface–ligand interface and the ligand molecular structures 10 . Therefore, the use of metal salt treatment provided a step to adjust the work function of colloidal NCs 31 . The removal of insulating organic layers and shortening interparticle distances help to enhance the electronic exchange coupling energy in NC solids and increase their packing density 12 .…”
Section: Resultsmentioning
confidence: 99%
“…Comparing average sizes of nanoparticles obtained by analyzing TEM images (∼5 nm in diameter) and average crystallite domain sizes obtained by applying the Scherrer equation to peaks in the diffractogram (∼4 nm in diameter) demonstrates that the surface layer is approximately 0.5 nm. Surface amorphization is seen in other studies as well, [43][44][45][46] including one which estimated the disordered surface layer thickness of Ni 2 P nanoparticles to be between 0.55 nm and 0.75 nm depending on surface facet terminations. 41 While it is not possible to model this disordered phase without additional information about its composition, the general effect of the nanoparticle surface, compared to the bulk, on the electronic structure can be modeled.…”
Section: Resultsmentioning
confidence: 69%
“…Papawassiliou et al found that (0001) surfaces dominate on Ni 2 P ultrasmall nanoparticles (4 nm in diameter), but (101̅0) surfaces dominate with larger nanoparticles (12 nm in diameter) . Even on the same facet (i.e., Ni 2 P­(0001)), there are multiple possible surface terminations (e.g., Ni 3 P 2 and Ni 3 P terminations). , In Figure , we summarize the computed HBE on Ni 2 P­(0001) ,,,, and CoP(101) , surfaces from reported values in the literature. The calculated HBE at the Ni 3 hollow site on the Ni 2 P­(0001) surface ranges from 0.137 eV to −0.543 eV.…”
Section: H Adsorption Site Diversity Arises From Structural Complexitymentioning
confidence: 96%
“…The structural complexity of TMP surfaces introduces several H adsorption sites with varying HBEs. The various stoichiometries and structures of TMPs range from metal-rich (e.g., Ni 3 P), equal amounts of metal and phosphorus (e.g., CoP), to P-rich (e.g., NiP 3 ), which are made possible by the highly covalent nature of metal–P bonds . In addition, the crystal structures themselves vary significantly, often with multiple distinct metal and/or P sites within a unit cell .…”
Section: H Adsorption Site Diversity Arises From Structural Complexitymentioning
confidence: 99%